Accelerating the elimination of viral hepatitis: a Lancet Gastroenterology & Hepatology Commission. (February 2019) - Cooke, Graham S; Andrieux-Meyer, Isabelle; Applegate, Tanya L; Atun, Rifat; Burry, Jessica R; Cheinquer, Hugo; Dusheiko, Geoff; Feld, Jordan J; Gore, Charles; Griswold, Max G; Hamid, Saeed; Hellard, Margaret E; et al.
Abstract : Viral hepatitis is a major public health threat and a leading cause of death worldwide. Annual mortality from viral hepatitis is similar to that of other major infectious diseases such as HIV and tuberculosis. Highly effective prevention measures and treatments have made the global elimination of viral hepatitis a realistic goal, endorsed by all WHO member states. Ambitious targets call for a global reduction in hepatitis-related mortality of 65% and a 90% reduction in new infections by 2030. This Commission draws together a wide range of expertise to appraise the current global situation and to identify priorities globally, regionally, and nationally needed to accelerate progress. We identify 20 heavily burdened countries that account for over 75% of the global burden of viral hepatitis. Key recommendations include a greater focus on national progress towards elimination with support given, if necessary, through innovative financing measures to ensure elimination programmes are fully funded by 2020. In addition to further measures to improve access to vaccination and treatment, greater attention needs to be paid to access to affordable, high-quality diagnostics if testing is to reach the levels needed to achieve elimination goals. Simplified, decentralised models of care removing requirements for specialised prescribing will be required to reach those in need, together with sustained efforts to tackle stigma and discrimination. We identify key examples of the progress that has already been made in many countries throughout the world, demonstrating that sustained and coordinated efforts can be successful in achieving the WHO elimination goals.